Immediate effects of short-term meditation on sensorimotor rhythm-based brain–computer interface performance - Kim, Jeehyun; Jiang, Xiyuan; Forenzo, Dylan; Liu, Yixuan; Anderson, Nancy; Greco, Carol M.; He, Bin (Frontiers in Human Neuroscience, 2022)
Previous works suggest that long-term meditation practices and an 8-week mindfulness-based stress reduction (MBSR) training have positive behavioral and neurophysiological effects on a user’s ability to control a sensorimotor rhythm (SMR)-based brain-computer interface (BCI). In this study, we investigated the immediate effects of a short, 20-minute meditation on SMR-based BCI control. Thirty-seven subjects performed several runs of one-dimensional cursor control tasks before and after two types of 20-minute interventions: one active mindfulness meditation exercise and one passive listening exercise. We found that there is no significant change in BCI performance following either 20-minute intervention. Moreover, the change in BCI performance between the meditation group and the control group was found to be not significant. The present results suggest that a longer period of meditation is needed to improve SMR-based BCI control.